PENERIMAAN KONSUMEN TERHADAP LIQUID BODY SOAP EKSTRAK TEMBAKAU DAN ANALISIS HARGA POKOK PRODUKSINYA - Andi Eko Wiyono; Winda Amilia; Ida Bagus Suryaningrat (JURNAL AGROTEKNOLOGI, 2019)
Liquid body soap is one of the soap products made from a mixture of oil and alkali in liquid form. Addition of tobacco extracts produces liquid body soap which has new characteristics. The existence of tobacco waste extracts can affect the level of consumer acceptance. The level of acceptance of panelists can be measured using hedonic testing. The purpose of this study was to determine the effect of adding tobacco waste extract to the reception of liquid body soap sensory quality attributes and calculating the cost of production. This research was conducted in two steps. The first stage was intended to determine the best formula based on panelists' acceptance. The design that has been used was the single factor Complete Random Design. The factors used in this study were variations in tobacco extract as much as 5%, 10%, and 15%. In the next stage, the cost of production was analyzed. The results showed that the addition of tobacco waste extract had no significant effect on panelists' acceptance of the sensory quality attributes of liquid body soap. The best treatment was obtained from the addition of tobacco waste extract as much as 5%. The cost of producing liquid body soap was Rp. 9.075,44. Consecutive total costs/ year, selling price, annual profit., and R / C ratio was Rp. 984.023.244,-; Rp. 11.000, -; Rp. 208.673.756,-; and 1,21. Keywords: panelists, tobacco extracts, sensory quality, cost of production